Foreign Teacher Education and its influences under the light of autobiographic narratives - Santa, Everton Vinicius de (BELT - Brazilian English Language Teaching Journal, 2010)
In the process of teaching/learning a second language, educators’ beliefs act meaningfully in their performance, in their pedagogical choices, and in the student/educator interaction. These beliefs can be modified over new experiences, since during his or her undergraduate course, the student-teachers have the opportunity to experience many different school settings. That said, this paper has the objective to present and discuss whether the school experience, as long as the educator is involved in the academic environment, affects the student-teacher's point of view. Thus, an autobiographic narrative is being presented, in order to reflect on how these beliefs act in the upcoming educators’ academic development and, throughout this plot, scan and point out some considerations about teaching/learning, using some educators’ and applied linguistics’ papers as basis, as well as their consideration about the discussion brought to light here. This paper forwards the importance of discussing teachers' beliefs.